Urban sustainability through environmental design : approaches to time-people-place responsive urban spaces - Thwaites, Kevin (Routledge, 2007)
What can architects, landscape architects and urban designers do to make urban open spaces, streets and squares more responsive, lively and safe? This title answers this question by providing the analytical tools and practical methodologies that can be employed for solutions to the design and management of urban environments.